2017
DOI: 10.1002/cam4.1254
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormone‐binding globulin (SHBG) is a potential early diagnostic biomarker for gastric cancer

Abstract: The use of blood plasma biomarkers in gastric cancer (GC) management is limited due to a lack of reliable biomarkers. An LC‐MS/MS assay and a bioinformatic analysis were performed to identify blood plasma biomarkers in a GC discovery cohort. The data obtained were verified and validated by western blotting and an ELISA in an independent study cohort. A label‐free quantification analysis of the MS data using PEAKS7 software found that four plasma proteins of apolipoprotein C‐1, gelsolin, sex hormone‐binding glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 46 publications
(58 reference statements)
1
11
0
Order By: Relevance
“…4 Speculatively, this could perhaps be due to the role of SHBG in limiting estradiol bioactivity, as estradiol has been shown to reduce the viability and carcinogenic potential of Helicobacter pylori in animal models. 44,45 Nevertheless, we are unable to rule out the possibility of reverse causation 46 or chance.…”
Section: Associations With Incident Cancer In Menmentioning
confidence: 85%
“…4 Speculatively, this could perhaps be due to the role of SHBG in limiting estradiol bioactivity, as estradiol has been shown to reduce the viability and carcinogenic potential of Helicobacter pylori in animal models. 44,45 Nevertheless, we are unable to rule out the possibility of reverse causation 46 or chance.…”
Section: Associations With Incident Cancer In Menmentioning
confidence: 85%
“…Speculatively, this may be due to the role of SHBG in limiting estradiol bioactivity, as estradiol has been shown to reduce the viability and carcinogenic potential of H. pylori in animal models (46,47). Nevertheless, we are unable to rule-out the possibility of reverse causation (48) or chance.…”
Section: Associations With Incident Cancer In Menmentioning
confidence: 88%
“…There are few reports that have investigated the association between SHBG and cancers. For example, Cheng and colleagues reported that plasma levels of SHBG are significantly increased in patients with gastric cancer, whereas Huang and colleagues suggested that higher expression of SHBG in ovarian cancer is a poor prognostic factor (38,39). Being female gender has been reported as a poor prognostic factor in patients with NMIBC (3,40).…”
Section: Discussionmentioning
confidence: 99%